BcGRP23: A novel gene involved in the chlorophyll metabolic pathway that is activated by BES1 in flowering Chinese cabbage - Zhang, Shuaiwei; Chen, Kemin; Anwar, Ali; Wang, Yudan; Yao, Shengyi; Chen, Riyuan; Song, Shiwei; Su, Wei (Frontiers in Plant Science, 2022)
Glycine-rich proteins (GRPs) are a large family of proteins, which play vital role in cell wall remodeling, cell metabolism and development, and abiotic stress responses. Although the GRPs functions in cell wall remodeling have been well characterized, few studies have evaluated the GPRs affect chlorophyll metabolism and response to hormone. Here, we investigated the molecular mechanism of BcGRP23 and participation in chlorophyll metabolism and BES1 signaling pathway in flowering Chinese cabbage. The results suggested that, the expression level of BcGRP23 in leaves and stems gradually decreased with increase of growth and development of flowering Chinese cabbage, and was barely not expressed after flowering. The GUS staining gradually became lighter in hypocotyls as the plants continued to grow, was largely free in growth points. The petioles and stems of BcGRP23-silenced plants appeared loss of green, and the contents of Chl a and Chl b were significantly reduced. Further research found that the expression of chlorophyll degradation-related genes was significantly increased in silenced plants compared with the control, while the results were the opposite in BcGRP23-overexpression lines. The BcGRP23 promoter sequence contains a large number of hormone-responsive elements; the expression of BcGRP23 was upregulated in flowering Chinese cabbage by treating with hormones such as IAA, GA, 6-BA, MeJA, BR, and was most significant in BR. BES1 (BRI1- EMS - SUPPRESSOR 1), response to BRs, directly activate the BcGRP23 promoter. Our findings indicated that BcGRP23 regulate the expression of chlorophyll degradation-related genes, thus affect chlorophyll contents; BcGRP23 was significantly regulated by exogenous BR application, and is directly activated by the BES1. These results preliminarily clarified the molecular mechanism and regulatory pathway of the BcGRP23 in flowering Chinese cabbage involved in plant growth and development and in response to environmental stress.